Applying quality control to daily habits: A new method for teaching quality control - Kabadurmus, Ozgur; Powell, Karsten; Vaughan, Timothy S. (Decision sciences journal of innovative education, 2025)
This teaching brief presents a new experiential exercise for teaching statistical process control (SPC) within a quality management course. This novel approach involves a semester‐long personal quality control project, where students apply SPC methodology to their daily habits, using data collected from their smart devices. Surveys conducted at the end of the semester show that students felt more confident using quality control concepts both personally and professionally. The survey results also suggest that students believe the exercise helped them to better understand their own daily habits and aided their ability to apply quality management methodologies through greater engagement with the concepts. This innovative teaching method both enhances students’ theoretical understanding and prepares them for effective problem‐solving in industry settings.